Evaluasi Pengobatan Radioterapi Pada Pasien Kanker - Herlinda Mahdania Harun; Nurul Jannah; Idawati Idawati; Zul Fikar Ahmad (Journal Syifa Sciences and Clinical Research, 2022)
Cancer is one of the leading causes of death in the world. Riskesdas data in 2018, that there is an increase in the prevalence of cancer in Indonesia every year and treatment with radiation/irradiation. The purpose of this study was to describe the characteristics (gender, age, education level, occupation), type of cancer, and duration of treatment as well as side effects obtained by cancer patients during or after radiotherapy treatment. The location of the research was carried out at the RSI. Faisal Makassar. This type of research is quantitative descriptive with consecutive sampling. Data was collected using medical records of cancer patients who underwent radiotherapy and then telephone interviews based on questionnaires. Data analysis in this study is descriptive quantitative univariate analysis to describe the distribution of each research variable. Research results obtained 49 cancer patients who underwent radiotherapy, the characteristics of the most respondents were the 46-52 year age group by 26.5% (13 people), female 71.4% (35 people), the last high school education was 44,9% (22 people), work as a housewife by 44.9% (22 people), the most type of cancer diagnosis is cervical cancer by 28.6% (14 people), the length of treatment received for 3 months is 40 times radiation treatment/therapy, and the perceived side effects of radiotherapy were weakness, pain, and dermatitis in the radiation area.